Use of a Gamified Platform to Improve Scientific Writing in Engineering Students - Rosa Núñez-Pacheco; Elizabeth Vidal; Eveling Castro-Gutierrez; Osbaldo Turpo-Gebera; Aymé Barreda-Parra; Ignacio Aguaded (MDPI AG, 2023)
The general purpose of this study was to determine the potential of using a gamified platform in the development of scientific writing skills among engineering students at a Peruvian university. To this end, a gamified web platform named Call for Papers for Engineers was designed. This platform contains mini-games focused on developing reading and writing skills for articles related to the engineering area. A quantitative methodological approach was employed, with a quasi-experimental design involving two groups: an experimental group and a control group, with pre-and post-test measurements. Additionally, the gamified platform was validated through expert judgment, and user satisfaction levels were assessed. The main results indicate that the content developed in the course and the use of the gamified web platform were effective teaching methods, as the students in the experimental group demonstrated higher performance after using the gamified platform compared to the control group. Furthermore, participants in the study expressed satisfaction with the use of this technological resource, finding it motivating and user-friendly.